Fishing the waters of life: Zane Grey's White Death, exploitation film and the Great Barrier Reef. Issue 1 (2nd January 2017) - Speed, Lesley
ABSTRACT: Edwin G. Bowen's White Death (1936) is an Australian–American film about shark fishing that stars the American novelist and fisherman Zane Grey as himself. Set mainly at the Great Barrier Reef, it has a semi-fictional plot about Grey's quest to kill a shark in the face of opposition from an anti-fishing activist, Newton Smith (Alfred Frith). Although White Death was financially unsuccessful and has received little attention in histories of Australian film or Grey's life, it is significant in several ways. The film is unusual among early Australian productions for combining elements of the genres of travelogue documentary, fictional adventure film and exotic exploitation film. It reflects an American perspective of Australia as an exotic location. White Death is also linked to the interwar development of tourism at the Great Barrier Reef and foreshadows the growth of the environmental conservation movement.